Using Linear Programming to Determine the Role of Plant- and Animal-Sourced Foods in Least-Cost, Nutritionally Adequate Diets for Adults - Chungchunlam SMS; Garrick DP; Moughan PJ (Oxford University Press on behalf of the American Society for Nutrition, 2021)
BACKGROUND: The respective roles of plant- and animal-sourced foods in sustainable healthy diets for humans remain unclear. Nutritional quality and the monetary cost of diets are key criteria among others for sustainable food production. OBJECTIVE: Linear programming (LP) was used to determine the composition of nutritionally adequate dietary patterns formulated at the lowest cost. The hypothesis tested was that animal-sourced foods would be included in least-cost diets due to their high density of particular essential nutrients. METHODS: The LP modeling work was based on eating patterns, retail food prices (2020), and the daily energy (11,150 kJ, 2665 kcal) and essential nutrient requirements (29 nutrients in total) of a reference adult in New Zealand (NZ). The LP modeling approach is publicly and freely available to readily illustrate the change in dietary profiles and daily diet cost, in the simulation of changes in energy and nutrient requirements, and price fluctuations within food groups. RESULTS: A nutrient-adequate, least-cost dietary pattern formulated from 883 foods, with a daily cost of NZ $3.23, included both animal- and plant-based foods. The nutrients found to be equally first-limiting were biotin, calcium, molybdenum, potassium, selenium, vitamin A, pantothenic acid, and vitamin C. When a dietary scenario with no animal-sourced foods was modeled, by increasing the retail prices of animal-sourced foods by 1.05 to 10.3 times, the daily cost of this plant-only dietary pattern was NZ $4.34. Additional nutrients, such as zinc, vitamin B-12, and vitamin D, were met at their daily minimum required levels. CONCLUSIONS: Dietary patterns formulated at the lowest cost and meeting the daily minimum requirements for energy and essential nutrients for an adult in New Zealand relied on foods sourced from animals and plants.
Keywords: adult; animal-sourced foods; diet affordability; diet cost; linear programming; nutrient adequacy